2019
DOI: 10.1021/acsami.8b18650
|View full text |Cite
|
Sign up to set email alerts
|

Doping as a Strategy to Tune Color of 2D Colloidal Nanoplatelets

Abstract: Among colloidal nanocrystals, 2D nanoplatelets (NPL) made of II-VI compounds, appear as a special class of emitters with especially narrow photoluminescence signal. However the PL signal in the case of NPL is only tunable by discrete step. Here we demonstrate that doping is a viable path to finely tune the color of this NPL from green to red, making them extremely interesting as phosphor for wide gamut display. In addition using a combination of luminescence spectroscopy, tight binding simulation, transport an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 51 publications
7
69
0
Order By: Relevance
“…In 2019, Ag‐doped CdSe NPLs prepared by a partial CE method were reported by two groups. [ 16,103 ] As shown in Figure 5d, Ag‐doped CdSe NPLs exhibit spectral tunability in the range of 609–880 nm, with a Stokes shift of up to 1 eV and a PLQY approaching 50%. [ 103 ] Identical to the control of the doping level in the Cu‐doped CdSe NPLs system mentioned earlier, the Ag doping level, reflected in PL spectroscopy results, could also be adjusted from loose surface doping to substantial substitution with a pristine lattice by monitoring the reaction time and amounts of doping impurities.…”
Section: Emission Tunability For Cdse‐based Nplsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Ag‐doped CdSe NPLs prepared by a partial CE method were reported by two groups. [ 16,103 ] As shown in Figure 5d, Ag‐doped CdSe NPLs exhibit spectral tunability in the range of 609–880 nm, with a Stokes shift of up to 1 eV and a PLQY approaching 50%. [ 103 ] Identical to the control of the doping level in the Cu‐doped CdSe NPLs system mentioned earlier, the Ag doping level, reflected in PL spectroscopy results, could also be adjusted from loose surface doping to substantial substitution with a pristine lattice by monitoring the reaction time and amounts of doping impurities.…”
Section: Emission Tunability For Cdse‐based Nplsmentioning
confidence: 99%
“…Previous studies on conventional quantum well semiconductors have shown that controlled doping with covalent elements is a powerful strategy to tailor the optoelectronic properties of materials of interest. [ 15 ] Inspired by the broad emission tunability by the introduction of dopant centers, controlled doping [ 16,17 ] has been used in CdSe NPLs to extend the emission wavelength to a wide range from 393 (purple) to 880 nm (deep red). Figure summarizes the resulting PL quantum yields (PLQY) and linewidths as a function of PL peak positions of the corresponding CdSe‐based NPLs prepared by different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since impurity-doped nanocrystals can show not only the intrinsic merits of nanocrystals but additional advantages (e.g., enhanced thermal and chemical stability, improved PLQY, and reduced Auger recombination) [148][149][150], they are generally considered as promising candidate emitters for LEDs with high efficiency and increased stability. For the impurity-doped ABX 3 perovskites, A-, B-, and X-site doping have been extensively applied to PeLEDs for high performance.…”
Section: Impurity Dopingmentioning
confidence: 99%
“…Generally, impurity-doped nanocrystals can exhibit not only the intrinsic merits of nanocrystals but also additional advantages including enhanced thermal and chemical stability, improved photoluminescence quantum efficiency (PLQY), reduced Auger recombination, impurity-related emission, and tailored charge mobility [ 59 , 60 , 61 , 62 , 63 ]. Owing to these superiorities, impurity-doped nanocrystals have sparked efforts to satisfy the requirement of many optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%